1989
DOI: 10.5558/tfc65114-2
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Existing Models for DBH Estimation from Large-scale Photos

Abstract: The performance of 12 diameter prediction models suggested in the literature was studied in a controlled operational test. These models were linear and logarithmic transformations of tree height and/or crown area and were analyzed for white spruce, lodgepole pine, and trembling aspen and balsam poplar combined. Overall, all models were statistically significant, with differences due to variations in species and model form. Although simpler models may be adequate depending on operational objectives, two models … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

1990
1990
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 4 publications
0
9
0
Order By: Relevance
“…Even with the high-spatial resolution aerial photographs, the direct measurement or the estimation of DBH was revealed to be quite difficult (Hagan and Smith, 1986;Hall et al, 1989). In addition, the correlation between Cpa and DBH of acacia forest in Australia revealed that the R 2 was only 0.42, which was quite weak (Lange and Sparrow, 1992).…”
Section: Stand Basal Areamentioning
confidence: 96%
“…Even with the high-spatial resolution aerial photographs, the direct measurement or the estimation of DBH was revealed to be quite difficult (Hagan and Smith, 1986;Hall et al, 1989). In addition, the correlation between Cpa and DBH of acacia forest in Australia revealed that the R 2 was only 0.42, which was quite weak (Lange and Sparrow, 1992).…”
Section: Stand Basal Areamentioning
confidence: 96%
“…Currently, both methods (digital stereo-photogrammetry and ALS) are suitable and enable estimation of H and CD at tree level [6,32]. Research on applicability of high-spatial resolution stereo-images [33][34][35][36] or high-density ALS data [14,37,38] for H estimation showed that H could be estimated with both methods with high accuracy and with no statistically significant difference compared to field measurements. Unlike H, it is more time-consuming and more difficult to accurately estimate crown size (area or diameter) of individual trees from remote sensing data, especially in densely canopied stands where overlapping of the crowns of the adjacent trees is common and complicates crowns measurement of individual trees [4,7,33,38,39].…”
Section: Discussionmentioning
confidence: 99%
“…Research on applicability of high-spatial resolution stereo-images [33][34][35][36] or high-density ALS data [14,37,38] for H estimation showed that H could be estimated with both methods with high accuracy and with no statistically significant difference compared to field measurements. Unlike H, it is more time-consuming and more difficult to accurately estimate crown size (area or diameter) of individual trees from remote sensing data, especially in densely canopied stands where overlapping of the crowns of the adjacent trees is common and complicates crowns measurement of individual trees [4,7,33,38,39]. Besides stand structure, estimated results of crown dimensions could be influenced by the pulse density of airborne laser scanning or spatial resolution of aerial images, but also by the computer algorithm used for crown delineation in cases when automatic method of delineation was used.…”
Section: Discussionmentioning
confidence: 99%
“…To estimate these values, tree crown areas and their corresponding CHM and P95 heights from locally validated samples were fit using local data in the following equation (Hall et al 1989):…”
Section: Height and Volume Comparisonmentioning
confidence: 99%